Can postoperative radiotherapy be omitted in localised standard-risk Ewing sarcoma? An observational study of the Euro-E.W.I.N.G group. (July 2016) - Foulon, Stéphanie; Brennan, Bernadette; Gaspar, Nathalie; Dirksen, Uta; Jeys, Lee; Cassoni, Anna; Claude, Line; Seddon, Beatrice; Marec-Berard, Perrine; Whelan, Jeremy; Paulussen, Michael; Streitbuerger, Arne; et al.
Abstract: Background: The role of postoperative radiotherapy (PORT) in Ewing sarcoma (ES) is unclear. We assessed the impact of PORT on local control in patients with localised ES and good histological response to chemotherapy (<10% cells). Patients and methods: All randomised patients in the EE99-R1 trial (comparing two consolidation chemotherapy regimens) undergoing surgery after induction chemotherapy were included. Local relapse (LR) cumulative incidence was estimated using a competing risk approach. Impact of PORT was assessed in multivariable models, adjusted for country, age, tumour site and volume, quality of resection and histological response. We also evaluated the heterogeneity of PORT effect by patient and tumour characteristics. Results: One hundred forty-two (24%) of the 599 patients included from 1999 to 2009 received PORT (median dose: 45 Grays). With median follow-up of 6.2 years, 67 patients had an LR (with concomitant metastases in 28), leading to an 8-year LR-incidence = 11.9% (standard error [se] = 1.4%). Overall survival (OS) = 21% (se = 5%) 3 years after LR (31% in isolated LR). Controlling for possible confounders, we observed a statistically significant reduction of LR in patients treated by surgery + PORT compared to surgery alone (subdistribution-hazard ratio = 0.43, 95% confidence interval, 0.21–0.88, p = 0.02). The benefit of PORT was particularly marked for tumours larger than 200 ml at diagnosis and 100% necrosis. We observed a non-significant trend for benefit associated with PORT for disease-free, event-free and OS. Conclusion: Radiotherapy appears to improve local control. We now recommend PORT in case of incomplete removal of the tissues involved by the pre-chemotherapy tumour volume. Further studies are required to assess the balance between benefit and risks. Highlights: We modelled the impact of postoperative radiotherapy (PORT) on local relapse (LR) in localised Ewing sarcoma. We observed a significant reduction of LR in patients treated by PORT compared to surgery alone. The benefit of PORT was particularly marked for tumours ≥ 200 ml and 100% necrosis. A non-significant trend for benefit was observed for disease-free survival, event-free survival and overall survival. We recommend PORT when pre-chemotherapy involved tissue volume cannot be entirely removed surgically.